Different degree of cytokinemia and T-cell activation according to serum IL-6 levels in critical COVID-19 - Lee, Chan Mi; Kim, Minji; Kang, Chang Kyung; Choe, Pyoeng Gyun; Kim, Nam Joong; Bang, Hyeeun; Cho, Taeeun; Shin, Hyun Mu; Kim, Hang-Rae; Park, Wan Beom; Oh, Myoung-don (Frontiers in Immunology, 2023)
Introduction: Tocilizumab, a humanized anti-interleukin-6 receptor (IL-6R) antibody, is recommended for the treatment of severe to critical coronavirus diseases 2019 (COVID-19). However, there were conflicting results on the efficacy of tocilizumab. Therefore, we hypothesized that the differences in tocilizumab efficacy may stem from the different immune responses of critical COVID-19 patients. In this study, we described two groups of immunologically distinct COVID-19 patients, based on their IL-6 response. Methods: We prospectively enrolled critical COVID-19 patients, requiring oxygen support with a high flow nasal cannula or a mechanical ventilator, and analyzed their serial samples. An enzyme-linked immunosorbent assay and flow cytometry were used to evaluate the cytokine kinetics and cellular immune responses, respectively. Results: A total of nine patients with critical COVID-19 were included. The high (n = 5) and low IL-6 (n = 4) groups were distinguished by their peak serum IL-6 levels, using 400 pg/mL as the cut-off value. Although the difference of flow cytometric data did not reach the level of statistical significance, the levels of pro-inflammatory cytokines and the frequencies of intermediate monocytes (CD14+CD16+), IFN-γ+ CD4+ or CD8+ T cells, and HLA-DR+PD-1+ CD4+ T cells were higher in the high IL-6 group than in the low IL-6 group. Conclusion: There were distinctive two groups of critical COVID-19 according to serum IL-6 levels having different degrees of cytokinemia and T-cell responses. Our results indicate that the use of immune modulators should be more tailored in patients with critical COVID-19.